THE EFFECT OF ZUMBA EXERCISE ON C-REACTIVE PROTEIN CONCENTRATION AND PERIPHERAL BLOOD PARAMETERS - Effendi, Agus Irfan; Kustarini, Indranila; Adhipireno, Purwanto; Sulistiyo, Yuli (Journal of Applied Health Management and Technology, 2025)
Maximum loads due to physical exercise cause a decrease in antibody production and a decrease in leukocyte function in general. Many studies have been conducted on the effects of physical exercise, including Zumba, on CRP levels and peripheral blood parameters, but the research results have yielded different conclusions. This study aimed to find out the effect of regular and irregular Zumba exercises on CRP concentration and peripheral blood examination parameters. This experimental study used a pre-test and post-test design. There were 30 females aged 18-40 years who were divided into 2 training groups. Group I Zumba training 5x/week and group II Zumba training 1x/week. Both groups had to practice 60 minutes/session for 6 weeks. After 6 weeks of intervention, there was no significant correlation of CRP concentration (p=0,100). There were significant differences in Hb concentration (p=0.035), leukocyte count (p=0.001), erythrocyte count (p=0.001), and platelet count (p=0.018) in both groups. There was no significant effect of RZ and IZ exercise on CRP concentration and leukocyte differential count. But there were significant differences in changes in Hb concentration, leukocyte count, erythrocyte count, and platelet count, after regular and irregular Zumba exercise.